2017
DOI: 10.3389/fpls.2017.02001
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Profiling Shows Divergent Gene Expression Patterns in Arabidopsis Grown under Different Densities

Abstract: Plants growing under high-density (HD) conditions experience increased competition for water, nutrients, and light, possibly leading to changes in size, biomass, morphology, and productivity. However, no research has focused on the relationship between whole-genome expression patterns and growth density. Here, we performed whole-genome RNA sequencing to examine the gene expression patterns in Arabidopsis grown under low and high densities. Of the 20,660 detected genes, the expression levels of 98 were enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In addition, it was found that the vertical position had a significant effect on gene expression when comparing planting densities. Guo et al sought out 205 genes that were considered to be differentially expressed in Arabidopsis grown under different planting densities [7]. Another study found that 221 genes exhibited differential expression in response to density stress in barley [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it was found that the vertical position had a significant effect on gene expression when comparing planting densities. Guo et al sought out 205 genes that were considered to be differentially expressed in Arabidopsis grown under different planting densities [7]. Another study found that 221 genes exhibited differential expression in response to density stress in barley [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate, as the main inorganic nitrogen source for plant growth and development, is not only a nutrient for plants, but can also act as a signaling molecule to regulate plant morphogenesis, physiological responses and gene expression [6365]. Guo et al showed that nitrate availability is the main factor limiting agricultural productivity under high density conditions [7]. Bouguyon et al found that the nitrate/nitrite transporter ( NRT1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides vegetative shade, high density planting also causes low R:FR light and induces SAS [ 31 ]. To further verify our results obtained from the shade experiment, we planted Arabidopsis plants under low to high densities and measured their Raman spectra.…”
Section: Resultsmentioning
confidence: 99%